Challenges to the design and testing of antimicrobial nanostructured surfaces - Elena P. Ivanova; Denver Linklater (Microbiology Australia, 2023)
Nanomaterials, specifically nano-topographies, have been explored for their antimicrobial activity toward bacteria, fungi and even viruses. A decade ago, we discovered that the nanopillar topography of insect wings such as cicadas, dragonflies and damselflies, were not repelling bacteria as previously surmised, but bacteria were attaching and consequently being killed. The nature of the bactericidal effect associated with nanostructured insect wings has been extended to include antimicrobial activity toward both to environmental and pathogenic fungi. Specifically, the antimicrobial nature is associated with the physical disintegration of attached microbes due to a mechanical stress imposed on the cell membrane, which stretches and breaks. This exciting new discovery implies that, if successfully replicated on the surface of biomaterials and implantable devices, systemic or local administration of antibiotics are no longer required to kill bacteria that attach on such surfaces.